Pengaruh Budaya Organisasi dan Promosi Jabatan terhadap Kinerja Karyawan PT. Taspen Kantor Cabang Utama Medan - Reza Nurul Ichsan; Lukman Nasution (Mahesa Research Center, 2020)
The purpose of this study was to determine whether there is influence of organizational culture and job promotion on employee performance at PT. Taspen (Persero) Kantor Cabang Utama Medan. The object of research is limited to organizational culture variable and job promotion as independent variable and employee performance as dependent variable. Samples, ie as many as 72 Respondents. Analysis method used is multiple linear regression analysis which kosntanta equal to 0,876 which means indicate that if variable of organizational culture and job promotion is considered constant then level of employee performance variable positive value that is equal to 0876. While the results of correlation coefficient X1 of 0.248 which means if the organizational culture has increased the employee performance will experience an increase of 0.248 and X2 coefficient of 0.851 which means that if job promotion variables increased the employee performance will experience an increase of 0.851, these three variables each have The relationship of positive attachment to employee performance and has a significant value is 0.000 <from 0.005.